Improving Digital and Health Literacy: The "E-Sehati" Program for the Family Welfare Empowerment Group of Sempaja Selatan - Abdul Hamid Kurniawan; Musdalifah Maulita; Rufina Hurai; Syafei Karim; Nurhasanah (Poltanesa, 2025)
The Family Welfare Empowerment (PKK) organization in Sempaja Selatan encounters several challenges, including gaps in digital access and suboptimal health conditions, where recurring floods often worsen public health issues. To overcome these problems, the E-Sehati program short for Business, Healthy Living, and Digital was introduced as an initiative to educate communities on digital technology use and to encourage clean and healthy living behaviors, especially among vulnerable populations. This research aims to design and assess the effectiveness of the E-Sehati program in enhancing digital literacy, particularly in relation to health behavior, and ultimately improving the community’s quality of life. The development of the E-Sehati program adopted the Waterfall model, which progresses through stages from analysis to evaluation. It focuses on educating participants about ten essential household health practices, including childbirth assisted by health professionals, exclusive breastfeeding, regular weighing of infants and toddlers, the use of clean water, proper handwashing, adequate sanitation, mosquito larvae control, daily exercise, balanced nutrition, and maintaining a smoke-free home environment. Data gathered through beta testing indicated that the program substantially enhanced participants’ digital literacy and encouraged healthier lifestyle habits. Overall, this study highlights the potential of multimedia-based health education and deepens understanding of how digital literacy and information technology can contribute to better household health outcomes.